Novel Spin‐Decoupling Strategy in Liquid Crystal‐Integrated Metasurfaces for Interactive Metadisplays. Issue 13 (1st May 2022) - Naveed, Muhammad Ashar; Kim, Joohoon; Javed, Isma; Ansari, Muhammad Afnan; Seong, Junhwa; Massoud, Yehia; Badloe, Trevon; Kim, Inki; Riaz, Kashif; Zubair, Muhammad; Mehmood, Muhammad Qasim; Rho, Junsuk
Abstract: Symmetric spin–orbit interaction (SOI)‐based approaches apply a practical limit on helicity multiplexed metaoptics, i.e., center symmetric information encoding. Contrarily, asymmetric SOI's based on the combination of geometric and propagation phase‐delay approaches can effectively address such limitations for multifunctional multiplexed metaoptics on the cost of design complexities. In this paper, a simple asymmetric SOI‐based technique is realized for multifunctional metaoptics, employing only a single unit cell, breaking the conventional tradeoff between design complexity and efficient asymmetric transmission efficiency. The design approach depends on geometric phase alone, which eases the fabrication challenges and decreases the computational cost associated with previous asymmetric SOI‐based metaoptics. Furthermore, this study utilizes a new, low‐cost CMOS‐compatible material to optimize the proposed single unit cell for low loss and high transmission efficiency over the complete visible domain. On‐axis and off‐axis holographic metasurfaces are designed and integrated with pressure‐sensitive liquid crystal cells to demonstrate actively tunable metaholography with no limitation of center symmetric information encoding. The simple design technique, cost‐effective fabrication, and finger touch‐enabled holographic output switching make this integrated setup a potential candidate for many applications such as smart safety labeling, motion or touch recognition, and interactive displays for impact monitoring of precious artworks and products. Abstract : Novel asymmetric spin–orbit interaction (SOI)‐based design strategy is reported to realize multifunctional metaoptics, breaking the conventional tradeoff between design complexity and efficient asymmetric transmission efficiency. It eases the fabrication challenges and decreases the computational cost associated with previous asymmetric SOI‐based metaoptics. Furthermore, the fabricated sample is integrated with pressure‐sensitive liquid crystal cells to demonstrate actively tunable metaholography without center symmetric information encoding limitation.